2006
DOI: 10.1139/t06-070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plastic fragments on hydraulic characteristics of pretreated municipal solid waste

Abstract: A systematic study was undertaken of the granular composition and hydraulic properties of municipal solid waste (MSW) produced by mechanical–biological pretreatment (MBP–MSW) from three different treatment plants with the aim of evaluating the potential application of MBP–MSW as an alternative barrier material for landfill final cover systems. Despite its coarse granular composition, MBP–MSW has low hydraulic conductivity. Long-term permeability tests show that the hydraulic conductivity decreases with time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In the case of saturated flow, the virtually impermeable plastic fragments embedded in the material obstruct the flow of fluids. The larger the amount and size of the plastic fragments, the greater the influence on permeability (Xie et al, 2006).…”
Section: Permeability Testsmentioning
confidence: 99%
“…In the case of saturated flow, the virtually impermeable plastic fragments embedded in the material obstruct the flow of fluids. The larger the amount and size of the plastic fragments, the greater the influence on permeability (Xie et al, 2006).…”
Section: Permeability Testsmentioning
confidence: 99%
“…2). Moisture content still seemed to be controlled by structure and bedding of the waste at the time of deposition causing preferential flow (Huber et al, 2004; Katers and Walczak, 2005; Xie et al, 2006). It is especially indicated at Erbenschwang.…”
Section: Resultsmentioning
confidence: 99%
“…Huber et al (2004) showed that most of the waste material revealed unchanged even after more than 15 yr since deposition by inadequate wetting, and that leachate analysis will therefore underestimate long-term emission potentials. In addition, Xie et al (2006) found that the hydraulic conductivity decreases with time in MSW landfi ll bodies. More than 500 g kg −1 of waste organic matter (WOM) were present in the carbohydrate fraction, the most suited compounds for microbial decay, still providing a high potential for methane emissions and energy production at the studied sites and in landfi ll sites of similar conditions in general despite more than 25 yr of rotting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, long periods of time are required to reach steady state conditions. Xie et al (2006) stated that, for a sample of similar size to that used in this test program (maximum particle size of 40 mm), the minimum time necessary to reach a steady state between inflow and outflow would be approximately 1 to 4 months. Durmusoglu et al (2006) determined that the hydraulic conductivity of wastes was not particularly sensitive to the applied hydraulic gradient.…”
Section: Waste Hydraulic Conductivitymentioning
confidence: 99%